The Swedish Kings of Cyberwar. - Eakin, Hugh (New York Review of Books, 2017)
The article discusses the U.S. NSA (National Security Agency) developing technical capability to gather secret information from all over the world. It states NSA in collaboration with Sweden's National Defense Radio Establishment FRA developed cyber warfare project Quantum operated through WINTER LIGHT, targeting computer or network. It states Edward Snowden exposed the mass surveillance carried out by governments in the name of national security highlighting the human rights violations.